A Stochastic First Purchase Diffusion Model: A Counting Process Approach - Böker, Fred (Journal of Marketing Research, 1987)
The diffusion rate of a first purchase diffusion model is interpreted as the intensity function of a counting process. Parameter estimation procedures are considered and some generalizations of the basic model are discussed.